[tex]$ \mbox{\large$11$ } $\\[/tex]
1.) In adding integers with different signs (positive + negative), you can rewrite the expression of adding a negative integer with a positive integer through transforming it into a subtraction sentence filled with positive integers.
⇒ [tex]$ \mbox{\Large$ (-15) + (26) = (26) + (-15) = 26 - 15 = \bold{11}$ } $\\[/tex]
2.) Therefore, the sum of [tex]-15[/tex] and [tex]26[/tex] is [tex]11[/tex].
I hope this helps you understand this concept in Mathematics.
Stay safe po.
#CarryOnLearning
#AnswerForTrees